Pathology of Co-contamination of Mycotoxins - Kalita, Jahnabi J; Arya, Rahul S; Rajkhowa, Tridib K; Gali, Jagan M; Samanta, Arup K (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study was conducted to investigate the pathology of naturally occurring co-contamination of mycotoxins in poultry farms and  the role of local management practices in the overall scenario. During the investigation, different chicken farms (n=73) in the Aizawl  district of Mizoram state (India) were surveyed and monitored for management practices, the occurrence of disease and mortality. The  feed samples collected from affected farms were tested for the presence of Aflatoxin and Ochratoxin by ELISA kits. The dead birds were  subjected to necropsy. Liver and kidneys from the dead birds were processed for histopathological studies. Ten feed samples out of 49  tested (20.4%) were found affected by co-contamination with Aflatoxin and Ochratoxin. In this study, the mean level of Aflatoxin and  Ochratoxin was 13.302 ppb and1.822 ppb, and the median level 12.143 ppb and1.674, ppb, respectively. Clinical signs were ruffled  feathers, depression, dullness, huddling, poor growth and , anorexia. Necropsy revealed pathological lesions in visceral and lymphoid  organs. Histopathological findings were inflammations, degenerative, and necrotic lesions in liver and kidneys. Poor management  practices were observed in affected farms. A perusal of available literature did not reveal any study on the presence of co-contamination  of Mycotoxicosis in poultry and poultry feed in Aizawl, Mizoram.
Keywords: Aflatoxin; Aizawl; ELISA; Ochratoxin; Pathology; Poultry